2019
DOI: 10.1186/s10086-019-1821-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and compressive strength of gypsum-bonded composites with papers, paperboards and Tetra Pak recycled materials

Abstract: The incorporation of recycled papers, paperboards and Tetra Pak as filling materials in brittle matrices presents an interesting approach in the utilization of waste materials for building construction. This paper examines the compressive strength and microstructure of gypsum-bonded wastepaper-based composites. Recycled wastepaper of various types (office paper, magazine paper and newspaper), cardboards, paper boxes and Tetra Pak were shredded to short length strips of about 4 × 18 mm. The shredded materials w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The results showed that the highest compressive resistance of 6.46 N/mm 2 belonged to the composites made with Tetra Pak® particles (size 4x18 mm), and a density of 1.29 g/cm3. This strength was 44% higher than that of the composite with magazine paper, which presented the lowest value (Foti et al, 2019).…”
Section: Waste Tetra Pak® Used In Building Materialsmentioning
confidence: 64%
“…The results showed that the highest compressive resistance of 6.46 N/mm 2 belonged to the composites made with Tetra Pak® particles (size 4x18 mm), and a density of 1.29 g/cm3. This strength was 44% higher than that of the composite with magazine paper, which presented the lowest value (Foti et al, 2019).…”
Section: Waste Tetra Pak® Used In Building Materialsmentioning
confidence: 64%
“…The results show a maximum compressive strength value of 6.46 N/mm 2 for gypsum/Tetra Pak mixtures, and a minimum value of 4.48 N/mm2 for gypsum/magazine paper mixtures. Regarding the maximum values, these composite materials could be applied to interior walls of buildings (Foti et al, 2019).…”
Section: Composite Materials Containing Waste Tetra Pakmentioning
confidence: 99%
“…In 2019 Foti et al [45] examined the compressive strength and microstructure of gypsum-bonded wastepaper-based composites. Recycled wastepaper of various types including aseptic cartons were shredded to short length strips of about 4 × 18 mm and used as filling materials in natural gypsum in a ratio of 1:3 (v/v), and water was added to the mix.…”
Section: Wall Claddingmentioning
confidence: 99%